Penetration Testing using Kali Linux: SQL Injection, XSS, Wordpres, and WPA2 Attacks - Teddy Surya Gunawan; Muhammad Kasim Lim; Mira Kartiwi; Noreha Abdul Malik; Nanang Ismail (Institute of Advanced Engineering and Science, 2018)
Nowadays, computers, smart phones, smart watches, printers, projectors, washing machines, fridges, and other mobile devices connected to Internet are exposed to various threats and exploits. Of the various attacks, SQL injection, cross site scripting, Wordpress, and WPA2 attack were the most popular security attacks and will be further investigated in this paper. Kali Linux provides a great platform and medium in learning various types of exploits and peneteration testing. All the simulated attack will be conducted using Kali Linux installed on virtual machine in a compuer with Intel Core i5 and 8 GB RAM, while the victim’s machine is the host computer which run Windows 10 version 1709. Results showed that the attacks launched both on web and firewall were conducted successfully.